Transposition in Garuda Magazine’s: English-Indonesian Translation - Cahya Dewi, Gusti Ayu Oka; Sudipa, I Nengah (Lingual Journal of Language and Culture; Vol 3 No 1 (2017), 2017)
The aims of this study are at (1) identifying methods of procedures mostly used and (2) describing the reasons why the data belongs to those procedures occurring in the two bilingual articles of Garuda Magazine. The data was collected by note taking and comparing techniques. The classification method for translation proposed by Vinay and Darbelnet (in Venuti) was used to analyze the collected data. Based on the analysis, four procedures were found in translation, those are: transposition, modulation, borrowing and literal translation. The result showed that method of transposition (17 data) was mostly applied in the article, due to the pursuit to achieve a closest natural equivalent. Therefore, such procedure cannot be avoided in translation. Keywords: transposition, modulation, Garuda Magazine.